2014
DOI: 10.1095/biolreprod.113.112649
|View full text |Cite
|
Sign up to set email alerts
|

The Death of Sertoli Cells and the Capacity to Phagocytize Elongated Spermatids During Testicular Regression due to Short Photoperiod in Syrian Hamster (Mesocricetus auratus)1

Abstract: In the Syrian hamster (Mesocricetus auratus), an animal that displays testicular regression due to short photoperiod, germ cells are removed by apoptosis during this process and the apoptotic remains are phagocytized by Sertoli cells. The aim of this work was to investigate morphologically whether the testicular regression process due to short photoperiod leads to the apoptosis of Sertoli cells, and whether, during testicular regression, the elongated spermatids are eliminated through phagocytosis by Sertoli c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
5
20
0
Order By: Relevance
“…Thus, it was observed that both apoptosis and proliferation play a key role in this phenomenon, as in the MR and SR stages there was a very significant increase in the apoptosis/proliferation ratio owing to increased apoptosis both in general and of each of the germ cell types as well as a decrease in proliferation during the onset of regression. This also correlated with observations made in the period when the apoptotic index in the Sertoli cells was maximum (Seco-Rovira et al, 2014). Later, in the TR group, this ratio is higher than in the controls, mainly at the expense of apoptosis of spermatocytes and spermatids because both the proliferative and apoptotic indexes of spermatogonia are similar to control values.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Thus, it was observed that both apoptosis and proliferation play a key role in this phenomenon, as in the MR and SR stages there was a very significant increase in the apoptosis/proliferation ratio owing to increased apoptosis both in general and of each of the germ cell types as well as a decrease in proliferation during the onset of regression. This also correlated with observations made in the period when the apoptotic index in the Sertoli cells was maximum (Seco-Rovira et al, 2014). Later, in the TR group, this ratio is higher than in the controls, mainly at the expense of apoptosis of spermatocytes and spermatids because both the proliferative and apoptotic indexes of spermatogonia are similar to control values.…”
Section: Discussionsupporting
confidence: 87%
“…The latter phenomenon is essential as it enables a minimal essential pool of spermatogonia to remain available to quickly restore the germinal epithelium during recrudescence. Besides, it should not be forgotten that the depletion of the seminiferous epithelium would be accompanied by the loss of Sertoli cells and the phagocytosis of late spermatids (Seco-Rovira et al, 2014), which would contribute to involution of the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it has been described that other lectins that bind to galactose residues are also positive towards apoptotic Sertoli cells in the spotted ray (Torpedo marmorata)" [55,68]. Therefore, our study, while confirming the usefulness of lectins to identify Sertoli cells undergoing apoptosis in mammals, shows that lectins can also identify their elimination during testicular regression, a fact that has also been observed in our laboratory using TUNEL and transmission electron microscopy [69]. Furthermore, during testicular regression, the Sertoli cell was observed to have a strong phagocytic capacity, which affected whole late spermatids [69].…”
Section: Apoptosis Identification In Seminiferous Epithelium Through supporting
confidence: 89%